Морфологические аспекты участия тучных клеток в формировании общего адаптационного синдрома - Арташян, О.С.; Юшков, Б.Г.; Храмцова, Ю.С. (Таврический медико-биологический вестник, 2012)
Реакція тучних клітин на стрес багато в чому визначається гіпоталамо-гіпофізарно-надниркової віссю ендокринної системи. При дії стрес-фактора відбувається її активація, що тягне за собою підвищений синтез гормонів наднирників, які впливають на функціональну активність тучних клітин, посилюючи їх дегрануляцію в тканинах. В адаптивних реакціях тучних клітин при дії екстремального фактора важливе місце займає міграція клітин з кісткового мозку і тимуса в периферичні органи і тканини. The response of mast cells to stress is largely determined by the hypothalamic-pituitary-adrenal axis of the endocrine system. The action of the stress factor activation occurs, which leads to an increased synthesis of adrenal hormones, which affect the functional activity of mast cells, increasing their degranulation in the tissues. In the adaptive responses of mast cells under the influence of extreme factors important one is the migration of cells from the bone marrow and thymus to peripheral organs and tissues.